2022
DOI: 10.2147/ppa.s348933
|View full text |Cite
|
Sign up to set email alerts
|

The Attitude, Perception, and Mental Health of Patients Receiving Orthodontic Treatment During the COVID-19 Pandemic in Saudi Arabia

Abstract: The COVID-19 pandemic has forced dental clinics to shut down indefinitely, leaving thousands of orthodontic patients in unending fear and dismay. The study aimed to assess the attitude, perceptions and mental health status of patients undergoing orthodontic treatment in Saudi Arabia during the lockdown. Patients and Methods: A cross-sectional study was conducted among orthodontic patients of different clinics across Saudi Arabia and selected using two-stage clustered sampling. A validated Arabic questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
1
5
0
1
Order By: Relevance
“…According to Cotrin et al, for 78% of orthodontic patients, it was important to avoid other people at the reception desk, while the availability of protective equipment for the patients was deemed important by 35% [ 18 ]. Similar results were published by Alassiry and Hakami, who reported that 76% of the respondents were not afraid to visit their dentist, under the condition that adequate preventive measures were followed [ 20 ].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…According to Cotrin et al, for 78% of orthodontic patients, it was important to avoid other people at the reception desk, while the availability of protective equipment for the patients was deemed important by 35% [ 18 ]. Similar results were published by Alassiry and Hakami, who reported that 76% of the respondents were not afraid to visit their dentist, under the condition that adequate preventive measures were followed [ 20 ].…”
Section: Discussionsupporting
confidence: 86%
“…The first studies in the field of dentistry that appeared after the outbreak of the pandemic were aimed at infection control under the new conditions [ 11 , 12 , 14 ]. Patient concern (for outcomes and duration of the treatment) was the topic of mostly orthodontic studies [ 18 20 ]. A few studies that emerged later provided data on the fear of dental patients during a pandemic, in addition to other information [ 21 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only with sufficient preventive precautions in place 76% of patients were willing to see a clinic after the lockdown. 18 Guo et al stated that most orthodontic appointments and problems were judged non-emergent during the outbreak, so most orthodontic departments and clinics were closed. Many orthodontists and patients were at home throughout the orthodontic practice suspension and home quarantine, communicating via smartphones or online telemedicine services.…”
Section: Evidence From Research Studiesmentioning
confidence: 99%